2011
DOI: 10.1002/ejoc.201100394
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Selective Sonogashira Reactions of 1,4‐Dibromo‐2‐fluorobenzene – Synthesis and Properties of Fluorinated Alkynylbenzenes

Abstract: A variety of alkynyl-substituted fluorinated benzene derivatives have been prepared by Sonogashira cross-coupling reactions of 1,4-dibromo-2-fluorobenzene. The reactions proceed with very good site-selectivity in favor of the 4-position because of electronic and steric reasons. The regioselectivity is explained by the results of DFT calculations. The absorption and emission (fluorescence) properties of the products,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Although site-selective Sonogashira reactions of 1,4-dibromo-2-fluorobenzene with 4-alkylbenzene acetylene was reported by Reimann [27] with satisfied yield of 80%, an inevitable dimer by-product appeared which is difficult to be isolated. In our work, fluoro derivatives of 1-iodo-4-bromobenzene were used as starting materials and a higher selectivity and yield were obtained.…”
Section: Resultsmentioning
confidence: 97%
“…Although site-selective Sonogashira reactions of 1,4-dibromo-2-fluorobenzene with 4-alkylbenzene acetylene was reported by Reimann [27] with satisfied yield of 80%, an inevitable dimer by-product appeared which is difficult to be isolated. In our work, fluoro derivatives of 1-iodo-4-bromobenzene were used as starting materials and a higher selectivity and yield were obtained.…”
Section: Resultsmentioning
confidence: 97%
“…It is observed that the absorbance maxima for 43 (λ max =321–331 nm) is higher than that of 42 (λ max =285–318 nm) [79] . This is attributable to the greater extended π‐conjugation in the former (Figure 1).…”
Section: Photophysical Properties Of Pahsmentioning
confidence: 93%
“…It is observed that the absorbance maxima for 43 (λ max = 321-331 nm) is higher than that of 42 (λ max = 285-318 nm). [79] This is attributable to the greater extended π-conjugation in the former (Figure 1). The compounds 42 e-f and 43 e-f containing tert-butyl and methoxy groups show redshift in absorption maxima when compared to 42 a and 43 a.…”
Section: Minireviewmentioning
confidence: 99%
See 1 more Smart Citation